Language Competences of Socially Maladjusted Youth - Ewa MAŁACHOWSKA (Communications of International Proceedings, 2021)
The European Pillar of Social Rights defines principles that aim to prepare every person to function in a rapidly changing world. A spectrum to achieve more democratic societies with greater equality. In order to achieve this goal, it is necessary to have the ability to communicate in speech and writing in various situations, as well as to control your way of communication and adapt it to the requirements of the situation. Developing the ability to understand and create information is the basis for further learning, which requires knowledge of vocabulary, grammar and language functions. Correct understanding and creating information, includes readiness for critical and constructive dialogue, sensitivity to aesthetic values and interest in interacting with other people. It is related to the awareness of the impact of language on other people and the need to understand and use language in a positive and socially responsible way. The research presented in the article concerns the language competences of adolescents in the context of their development and functioning. The conducted research is an answer to the state of linguistic and communicative competences of Polish youth and whether they have the ability to distinguish and use sources of various types, to search, collect and process information, to use appropriate aids, and to formulate and express their arguments in speech and writing in a convincing manner, according to context, whether they are sufficient for inclusive and sustainable economic growth, social cohesion and further development of a democratic culture.